Antibiotic resistance and siderophores production by clinical Escherichia coli strains - Mohamed Khazaal; Hoda H. El-Hendawy; Mona I. Mabrouk; Ahmed H. I. Faraag; Marwa R. Bakkar (BioTechnologia, 2022)
The phenomenon of antibiotic resistance has dramatically increased in the last few decades, especially in enterobacterial pathogens. Different strains of Escherichia coli have been reported to produce a variety of structurally different siderophores. In the present study, 32 E. coli strains were collected from different clinical settings in Cairo, Egypt and subjected to the antibiotic susceptibility test by using 19 antibiotics belonging to 7 classes of chemical groups. The results indicated that 31 strains could be considered as extensively drug-resistant and only one strain as pan drug-resistant. Siderophores production by all the tested E. coli strains was determined qualitatively and quantitatively. Two E. coli strains coded 21 and 49 were found to be the most potent siderophores producers, with 79.9 and 46.62%, respectively. Bacterial colonies with cured plasmids derived from strain 49 showed susceptibility to all the tested antibiotics. Furthermore, E. coli DH5α cells transformed with the plasmid isolated from E. coli strain 21 or E. coli strain 49 were found to be susceptible to ansamycins, quinolones, and sulfonamide groups of antibiotics. In contrast, both plasmid-cured and plasmid-transformed strains did not produce siderophores, indicating that the genes responsible for siderophores production were located on plasmids and regulated by genes located on the chromosome. On the basis of the obtained results, it could be concluded that there is a positive correlation between antibiotic resistance, especially to quinolones and sulfonamide groups, and siderophores production by E. coli strains used in this study.